Different determinants of vascular and nonvascular deaths in patients with atrial fibrillation: A SAKURA AF Registry substudy. Issue 3 (March 2019) - Kuronuma, Keiichiro; Okumura, Yasuo; Yokoyama, Katsuaki; Matsumoto, Naoya; Tachibana, Eizo; Oiwa, Koji; Matsumoto, Michiaki; Kojima, Toshiaki; Hanada, Shoji; Nomoto, Kazumiki; Arima, Ken; Takahashi, Fumiyuki; et al.
Highlights: Of 3237 patients, 200 (6.2%) died during a median 39.3 months follow-up period. Patients succumbed mainly to cardiac death, malignancy, or respiratory infection. The major determinants of vascular and nonvascular deaths differed slightly. Abstract: Background: The incidence and causes of death among patients in Japan treated for atrial fibrillation (AF), a major determinant of strokes and death, with direct oral anticoagulants (DOACs) are unclear. This study's aim was two-fold: to compare the incidence and causes of death between DOAC and warfarin users in Japan and to identify the factors associated with vascular and nonvascular death in the Japanese AF population. Methods: The study was based on the SAKURA AF registry, in which clinical events were tracked in 3267 enrollees from 63 institutions for 2–4 years. Enrollees included warfarin users ( n = 1577) and users of any of 4 DOACs ( n = 1690). The incidence, cause, and major determinants of death were analyzed. Results: During a median 39.3-month follow-up, 200 patients died, with most succumbing to cardiac death (25%), malignancies (21%), or respiratory infections (20%). There was no significant difference in deaths from any cause between warfarin and DOAC users (108 vs. 92 patients, p = 0.34). An age ≥75 years was found to be a major determinant of death, but the relative risk (vs. <75 years) was greater for nonvascular death (hazard ratio: 2.85 and 4.97 for age 75–84 and ≥85 years, respectively) than vascular death (2.14 and 2.98 for 75–84 and ≥85 years, respectively). Heart failure, renal dysfunction, and the type of institution were major determinants of vascular death, and a male sex, weight <50 kg, and anemia were major determinants of nonvascular death. Conclusions: The results of our AF registry-based study, in which two thirds of the enrolled patients succumbed to cardiac death, malignancies, or respiratory infections within 2– 4 years and use of DOACs rather than warfarin did not reduce the mortality, indicated that a management of AF that includes prophylaxis for vascular and nonvascular events in addition to strokes is warranted.